Analisis Penjadwalan Proyek Menggunakan Metode Pert Dan Fast Track Dari Hasil Pembangunan Kek Mandalika Paket 1 - Nano Suharyono; Rachmat Mudiyono; Sumirin (Journal of Mandalika Literature, 2025)
Development in the Mandalika Special Economic Zone (KEK) has several work packages, one of which is Package 1 which during the implementation process there were several obstacles that had a major impact on the postponement of the planned construction schedule for the project running from June 15, 2024 to June 10, 2023, postponed to September 30, 2023. The PERT method itself is to find out the time needed for the construction of package 1. The result is that there is a difference in the time needed to complete the MUTIP Package 1 project. For the Baseline for the completion time of the MUTIP package 1 work, it is known that the planned completion time is 831 days or starting from June 15, 2021 to June 10, 2023 (accuracy 86.62%). Meanwhile, the completion time of the work after being calculated using the PERT method requires a completion time of 831 days starting from June 15, 2021 to September 24, 2023 (accuracy 99.28%). and the acceleration carried out using the Fast Track method is known to require 724 days. So it can be concluded that the calculation of time using the PERT method and acceleration using the Fast Track method is more effective when used for the conditions that occur in the MUTIP Package 1 development project at the Mandalika Special Economic Zone.